The genetic structure of Mycobacterium tuberculosis - insights into genome organisation and evolution of the causative agent of tuberculosis - Brosch, Roland (Henry Stewart Talks, 2013)
Mycobacterium tuberculosis, genome information, essential genes- virulence genes, type VII secretion system involved in virulence and host pathogen interaction- genomics and evolution of tuberculosis-causing mycobacteria